Usability Evaluation OVO Electronic Wallet Application Using Usability Testing and Usefulness, Satisfaction, Ease Of Use Questionnaire - Prakoso, Handika Cahyo; Iqbal, Mohammad; Kurniawati, Ana (International Journal of Computer Sciences and Engineering, 2020)
Electronic wallet technology provides efficiency, flexibility, and security in every electronic transaction. OVO is one of several electronic wallets in Indonesia. Other electronic wallets in Indonesia are Jenius, Gopay, and Dana. This research aims to examine the usability parameters of OVO electronic wallet application using usability testing method and usefulness, satisfaction, and ease of use questionnaire approach. This research begins with some user reviews on google playstore mention that using OVO application to make payments is considered less effective and efficient. Data in usability testing collected through task testing and interviews with 9 respondents. Usefulness, satisfaction, and ease of use questionnaire approach done by distribute the questionnaire to 100 respondents. Qualitative data is presented by descriptive sentences, while quantitative data is processed by statistically and mathematically using tools such as Microsoft Excel and SPSS software. Results of this research are values for 7 parameters. The process status parameter has a success rate of 86 percent, while the process time parameter has an efficiency of 0.03 goals per second. Interview results represent the problem parameters by showing OVO applications deficiency on notification side, login method, and interface layout consistency. Usability of OVO applications according to usefulness, satisfaction, and ease of use questionnaire results is 81.46 percent. The parameters of usefulness, ease of use, ease of learning, and satisfaction produce a good value for OVO applications.